Phenotypic Variation and Long‐Term Outcome in Children With Congenital Hepatic Fibrosis - Dinesh Rawat; Déirdre Kelly; David V. Milford; Khalid Sharif; Carla Lloyd; Patrick McKiernan (2013)
Congenital hepatic fibrosis (CHF) and Caroli syndrome are frequently associated with renal cystic diseases. They have a variable clinical course, and the natural history is not well defined despite molecular advances. Our study describes the clinical manifestations and long-term outcome in children with this disorder.A retrospective case review of children with CHF at a single centre diagnosed on the basis of clinical features, radiological and endoscopic evidence of portal hypertension (PHT), and compatible histopathological findings. Children were categorised based on hepatic phenotype-group 1 (Caroli syndrome) and group 2 (CHF). Hepatobiliary as well as renal manifestations were recorded at presentation, and their evolution followed up until transplant or last follow-up.There were 40 children (22 boys) with a median age of 1.3 years at clinical presentation. Fourteen of 40 (35%) children presented in the neonatal period with primarily renal disease, of whom 11 (78%) had Caroli syndrome (P = 0.02). Significant PHT with oesophageal varices was seen in 86%, with no difference in the incidence of gastrointestinal bleeding and varices between Caroli syndrome and CHF. Cholangitis developed in 10 of 40 (25%) and was more common in the Caroli syndrome group (P = 0.009). A higher proportion of children with Caroli syndrome developed chronic kidney disease (CKD) stage 3 and above as compared with CHF (85% vs 42%; P = 0.007). Twelve of 21 (57%) and 8 of 19 (42%) children in the Caroli syndrome and CHF groups required either combined liver-kidney or isolated liver transplant, with the most common indication for renal transplantation being end-stage renal disease (CKD5d) with or without advanced PHT or cholangitis. All 14 (100%) children with neonatal presentation developed CKD5d and required combined liver-kidney transplant before 14 years of age, whereas 77% of children presenting beyond the neonatal period survived without liver-kidney transplant (P < 0.001). Neonatal presentation was the best predictor of the need for transplant.Caroli syndrome is more likely to present in the neonatal period and these patients are more likely to develop CKD5d. CKD stage 3 or above with recurrent cholangitis is more common in Caroli syndrome presenting beyond the neonatal period and adds to the significant morbidity in these patients. Children presenting in the neonatal period have a more severe phenotype and should be considered early for combined liver-kidney transplant.